Supramolecular interactions in graphene–chitosan composites with plasmonic nanoparticles - Sarah Briceño; Lorena Layana; Charlotte Berrezueta-Palacios; Lenin Andres Guerrero-León; Claudia Kroeckel; Duncan John Mowbray; Julio C. Chacón-Torres (Carbon Trends)
The supramolecular interactions between graphene and biopolymers, such as chitosan, determine both whether nanostructured-hybrid materials are formed and their technologically relevant physical/chemical properties. However, there is still a fundamental lack of knowledge about how nanocomposites based on chitosan and graphene are formed, as well as their intrinsic structure and interaction with plasmonic nanoparticles. In this work, we provide an in-depth understanding of the supramolecular interactions between chitosan and graphene in the formation of graphene–chitosan nanocomposites with gold or silver nanoparticles. To do so, we employ a combination of Raman spectroscopy, Fourier-transformed infrared (FTIR) spectroscopy, atomic force microscopy (AFM), scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS) measurements with density functional theory (DFT) calculations to reveal the mechanism and driving forces behind these supramolecular interactions between graphene and chitosan. Specifically, we show they are based on a charge transfer process derived from the protonation of the amine groups of chitosan in acidic media. The understanding of the supramolecular interaction between graphene and chitosan that we provide herein should prove of great importance and interest to the material sciences and biomedical engineering fields.